Cervical cancer risk in women living with HIV across four continents: A multicohort study. Issue 3 (19th June 2019) - Rohner, Eliane; Bütikofer, Lukas; Schmidlin, Kurt; Sengayi, Mazvita; Maskew, Mhairi; Giddy, Janet; Taghavi, Katayoun; Moore, Richard D.; Goedert, James J.; Gill, M. John; Silverberg, Michael J.; D'Souza, Gypsyamber; et al.
Abstract : We compared invasive cervical cancer (ICC) incidence rates in Europe, South Africa, Latin and North America among women living with HIV who initiated antiretroviral therapy (ART) between 1996 and 2014. We analyzed cohort data from the International Epidemiology Databases to Evaluate AIDS (IeDEA) and the Collaboration of Observational HIV Epidemiological Research in Europe (COHERE) in EuroCoord. We used flexible parametric survival models to determine regional ICC rates and risk factors for incident ICC. We included 64, 231 women from 45 countries. During 320, 141 person‐years (pys), 356 incident ICC cases were diagnosed (Europe 164, South Africa 156, North America 19 and Latin America 17). Raw ICC incidence rates per 100, 000 pys were 447 in South Africa (95% confidence interval [CI]: 382–523), 136 in Latin America (95% CI: 85–219), 76 in North America (95% CI: 48–119) and 66 in Europe (95% CI: 57–77). Compared to European women ICC rates at 5 years after ART initiation were more than double in Latin America (adjusted hazard ratio [aHR]: 2.43, 95% CI: 1.27–4.68) and 11 times higher in South Africa (aHR: 10.66, 95% CI: 6.73–16.88), but similar in North America (aHR: 0.79, 95% CI: 0.37–1.71). Overall, ICC rates increased with age (>50 years vs . 16–30 years, aHR: 1.57, 95% CI: 1.03–2.40) and lower CD4 cell counts at ART initiation (per 100 cell/μl decrease, aHR: 1.25, 95% CI: 1.15–1.36). Improving access to early ART initiation and effective cervical cancer screening in women living with HIV should be key parts of global efforts to reduce cancer‐related health inequities. Abstract : What's new? Invasive cervical cancer (ICC) is a significant burden among women living with human immunodeficiency virus (HIV). Little is known, however, about geographical differences in ICC rates in women living with HIV. Here, ICC incidence rates in women who received antiretroviral therapy (ART) were compared across geographic regions. ICC incidence was notably high among women living with HIV in South Africa and Latin America. Five years after ART initiation, ICC incidence remained elevated for women in these two regions, compared with women in Europe and North America. Reduced CD4 cell count and older age at ART initiation were associated with increased ICC risk.